CELEBRITY ENDORSEMENT ON MILLENNIAL CUSTOMERS’ PURCHASING BEHAVIOUR - Mohd Amirul Atan; Fadhilah Zainal Abidin; Farith Azizi Mohayyaddin Abdul Kader; Natthaphon Santhi; Kannikar Kantamas; Mohd Isham Abidin (International Journal of Accounting, Finance and Business, 2021)
The study reviews relevant literatures in relation to the phenomenon of celebrityendorsement towards millennial customers’ purchasing behaviour. Literatures based on thevariables of endorser’s gender, credibility, attractiveness and type) were reviewed in obtainingthe overviews of the phenomenon based on past studies. In addition, related literatures oncustomer purchasing behaviour were also reviewed. This study also includes an overview ofcelebrity endorsement from the perspective of Thailand’s purchasing behaviour context. Basedon the reviews made, some suggestions and recommendations related to the phenomenon aremade as a guide for individu